Redescription of species of Gongylonema Molin, 1857 (Nematoda: Spiruroidea: Gongylonematidae) parasitic in some Australian vertebrate hosts and description of three new species - Spratt, David M. (Zootaxa, 2023)
Gongylonematid nematodes (Nematoda: Gongylonematidae) parasitic in some Australian vertebrates are described from the monotypic genus Gongylonema (Gongylonema) (Molin, 1857). Three previously incompletely described species from a megapod and murid rodents are re-described from limited material. Three additional species are described from murid rodents and macropodid, potoroid and phalangerid marsupials. A key to species is provided.